2022
DOI: 10.31083/j.rcm2309304
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Erectile Dysfunction and Co-Morbidities: “The Good, the Bad and the Ugly”

Abstract: Erectile dysfunction (ED), defined as the inability to attain or maintain sufficient penile erection for sexual intercourse, is a growing health problem, which unfortunately remains underreported, underdiagnosed and undertreated. Growing evidence suggests that ED is a promising cardiovascular risk marker, as it is associated with major co-morbidities increasing cardiovascular disease burden, while it is an independent predictor of cardiovascular morbidity and mortality. The role of exercise as a non-pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
2
1
Order By: Relevance
“…However, there was no statistically significant association between low testosterone levels and ED, probably because most of the participants had low testosterone. HIV can cause low testosterone, although currently, the relationship between HIV and testosterone is a controversial one, as other studies have found normal testosterone levels in men living with HIV (25,26). Dyslipidemia was not associated with ED in MLHIV in this study, contrary to evidence from a study in Mexico (10).…”
Section: Discussioncontrasting
confidence: 99%
“…However, there was no statistically significant association between low testosterone levels and ED, probably because most of the participants had low testosterone. HIV can cause low testosterone, although currently, the relationship between HIV and testosterone is a controversial one, as other studies have found normal testosterone levels in men living with HIV (25,26). Dyslipidemia was not associated with ED in MLHIV in this study, contrary to evidence from a study in Mexico (10).…”
Section: Discussioncontrasting
confidence: 99%
“…It is interesting, however, that we failed to see any consistent effects of meeting WHO recommended weekly exercise levels (i.e., at least 3 times a week with moderate intensity). This was surprising given that physical activity has been shown to benefit inflammation in both healthy people and CVD patients [62,63], and shown to benefit endothelial function [28][29][30][31] and ED [24,26,[64][65][66]. Self-reported levels of physical activity may not reliably reflect the true duration and intensity of participants' exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiorespiratory fitness offers significant protection against ED [23], and several reviews have concluded on protective effects of aerobic exercise [24][25][26]. The benefits of physical activity on vascular health and CVD are well supported in the medical literature [12,27].…”
Section: Introductionmentioning
confidence: 99%